Analisis firewall sebagai bandwidth limiter dan network security menggunakan pfsense - Agung Wirjawan; Hilman Iskandar; Rahmad Hidayat; Dwiyanto Dwiyanto; Ike Yuni Wulandari; Yudi Herdiana (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Internet connections that are not always stable and data security is not maintained from various threats from outside attacks in the form of hackers, crackers, viruses, and so on are the main problems for every client. Using the pfSense analysis method, this study aims to address the above bandwidth management and network security issues. The pfSense analysis that the researchers carried out included an analysis of total bandwidth usage, data security, and information for each client on the P3DW Internet network (Center for Regional Revenue Management) Bandung III Soekarno-Hatta City. The results of the analysis concluded that pfSense can work as a firewall that functions as a bandwidth limiter and network security. The level of client satisfaction increases with the infrastructure designs being tested. With a web GUI that makes it easy for users to configure, the basic system used is FreeBSD which is open-source, making pfSense able to be an alternative choice for building a firewall that is reliable, flexible, and economical.